Integrative network pharmacology and experimental verification to reveal the anti-inflammatory mechanism of ginsenoside Rh4 - To, Kwang-Il; Zhu, Zhen-Xing; Wang, Ya-Ni; Li, Gang-Ao; Sun, Yu-Meng; Li, Yang; Jin, Ying-Hua (Frontiers in Pharmacology, 2022)
Inflammation is an innate immune response to infection and it is the main factor causing bodily injury and other complications in the pathological process. Ginsenoside Rh4(G-Rh4), a minor ginsenoside of Panax ginseng C. A. Meyer and Panax notoginseng, has excellent pharmacological properties. However, many of its major pharmacological mechanisms, including anti-inflammatory actions, remain unrevealed. In this paper, network pharmacology and experimental approach were employed to elucidate the drug target and pathways of G-Rh4 in treating inflammation. The potential targets of G-Rh4 were selected from the multi‑source databases, and 58 overlapping gene symbols related to G-Rh4 and inflammation were obtained for generating a protein-protein interaction（PPI）network. Molecular docking revealed the high affinities between key proteins and G-Rh4. Gene ontology (GO) and pathway enrichment analyses were used to analyze the screened core targets and explore the target-pathway networks. It was found that JAK-STAT signaling pathway, TNF signaling pathway, NF-κB signaling pathway, Th17 cell differentiation, and PI3K-Akt signaling pathway may be the key and main pathways of G-Rh4 to treat inflammation. Additionally, the potential molecular mechanisms of G-Rh4 predicted from network pharmacology analysis were validated in RAW264.7 cell inflammatory response. RT PCR, Western blot, and ELISA analysis indicated that G-Rh4 significantly inhibited the production of pro-inflammatory cytokines such as TNF-α, IL-6 and IL-1β, as well as inflammation-related enzymes in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Moreover, in vitro experiments evaluated that Ginsenoside Rh4 exerts anti-inflammatory effects via the NF-κB and STAT3 signaling pathways. It is believed that our study will provide the basic scientific evidence that G-Rh4 has potential anti inflammatory effects for further clinical studies.